Evaluation of the influence of sowing depth and of substrates in the production of seedlings of mutamba (Guazuma ulmifolia Lam. Malvaceae) - Cruz, Temile Santana; Cruz, Ane Caroline Rocha; Ribas, Dayane Gabriela de Lima; Oliveira, Fábio; Cocozza, Fábio del Monte (MAGISTRA, 2017)
In the propagation of plant species, depth and substrate are conditions needed for seed germination and seedling development. Therefore, this study evaluated the effects of the influence of different depths on germination of Guazuma ulmifolia Lam seeds as well as the seedling production, using different substrates. For analysis of depth and substrate, it was used the design in randomized blocks (DBC); in both analyzes were used 5 treatments, 4 replicates and 25 seeds per plot. In the test, the seeds were sown at different depths (cm): P1 - Witness (seeds exposed at the surface); P2 - 0.5; P3 - 1.0; P4 - P5 and 2,0 - 3,0. In the analysis of substrate, the treatments were: 80% of soil and 20% of wood shavings (S1 - Witness); 80% of soil and 20% of washed sand (S2); 80%of soil and 20% of cattle manure (S3); 100% of soil (S4); 80% of soil and 20% of sawdust (S5). The variables analyzed were: Emergency Speed Rate (ESR), height (cm), number of leaves, lap diameter (mm), root length (cm), fresh and dry weight of shoot, fresh and dry weight of root (g). It was found that the depth of 0.5 to 1.0 cm presented a faster speed of emerging seedlings. The treatment with 80% of soil and 20% of cattle manure showed better development for plants.